2018
DOI: 10.1152/ajplung.00439.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface phenotyping identifies CD36 and CD97 as novel markers of fibroblast quiescence in lung fibrosis

Abstract: Fibroblasts play an important role in lung homeostasis and disease. In lung fibrosis, fibroblasts adopt a proliferative and migratory phenotype, with increased expression of α-smooth muscle actin (αSMA) and enhanced secretion of extracellular matrix components. Comprehensive profiling of fibroblast heterogeneity is limited, due to a lack of specific cell-surface markers. We have previously profiled the surface proteome of primary human lung fibroblasts. Here, we sought to define and quantify a panel of cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…There are few studies in literature that tackle the surface proteome profiling in different organs, to key cellular events in oncogenesis or metastasis development. Facts with reference to a potential common contribution of CD36 and CD97 were revealed firstly by Heinzelmann et al [95]. They studied expression changes in different CD markers profile in lung fibrosis, with a major emphasis on specific phenotypes during fibroblast-myofibroblast activation by TGFβ, known to express αSMA (α-smooth muscle actin).…”
Section: Why Examine Concomitant Expression Of Cd36 and Cd97s? (Why Bmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few studies in literature that tackle the surface proteome profiling in different organs, to key cellular events in oncogenesis or metastasis development. Facts with reference to a potential common contribution of CD36 and CD97 were revealed firstly by Heinzelmann et al [95]. They studied expression changes in different CD markers profile in lung fibrosis, with a major emphasis on specific phenotypes during fibroblast-myofibroblast activation by TGFβ, known to express αSMA (α-smooth muscle actin).…”
Section: Why Examine Concomitant Expression Of Cd36 and Cd97s? (Why Bmentioning
confidence: 99%
“…It was also observed that CD36-and CD97-positive population decreased upon TGFβ stimulation and was part of a senescent population, as well, being significantly increased in high passages. The simultaneous presence of quiescent and activated fibroblasts could be mirrored by dynamic changes in surface markers; thus, different fibroblast phenotypes are characterized by various combinations of CD expression [95].…”
Section: Why Examine Concomitant Expression Of Cd36 and Cd97s? (Why Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been made to better characterize the lung mesenchymal population and their heterogeneity, although the absence of a single, well-defined marker poses a challenge in quantifying their relative contributions to myofibroblasts [47][48][49]. In a study using signal transduction pathway readouts to define mesenchymal heterogeneity and lineages, Zepp et al identified several lineages of mesenchymal cells with distinct transcriptional and functional properties during homeostasis and following injury [45•].…”
Section: Resident Mesenchymal Cellsmentioning
confidence: 99%
“…Senescent cells have been reported in both human and animal models of pulmonary diseases (1,4,19,21,24,25,34,42,47,59,61,63). What is less clear is the extent to which phenotypic changes associated with normal chronological aging or in disease states are mechanistically attributable to cellular senescence or effects of senescent cells per se, i.e., how important are senescent cells in pathophysiology?…”
mentioning
confidence: 99%